Description of the Immatures of Workers of the Ant Linepithema micans Forel (Hymenoptera: Formicidae) - Nondillo, Aline [UNESP]; Solis, Daniel Russ [UNESP]; Paterson Fox, Eduardo Goncalves; Rossi, Monica Lanzoni; Botton, Marcos; Bueno, Odair Correa [UNESP] (Wiley-Blackwell, 2011)
Linepithema micans Forel is a poorly studied species that is now considered a pest in vineyards in South Brazil. Larval characters have been used in a few phylogenetic studies, and their importance greatly depends in the amount of available information on different species. This study presents a complete panorama on the external morphology of the immatures of L. micans based on observations by light and scanning electron microscopy. The number of larval instars was estimated as three based on the frequency distribution of head widths of 965 larvae. Larvae of L. micans were similar to other Linepithema Mayr in the general format of body and mandibles, presenting a dorsal abdominal protuberance, nine pairs of spiracle, and unbranched hairs. on the other hand, L. micans was unique for having shorter hairs, predominantly denticulate, intraspecific variation in the number of antennal sensilla and in the types of sensilla on the labial palps were reported. Microsc. Res. Tech. 74:337-342, 2011. (C) 2010 Wiley-Liss, Inc.
Keywords: larvae; Dolichoderinae; Humile group; Linepithema dispertitum micans; morphology